Challenging e-Learning in the University. - Goodfellow, Robin, 1947- (McGraw-Hill International (UK) Ltd., 2007)
Takes a fresh approach to the field of e-learning in higher education. This work gives an alternative perspective to e-learning. It argues that in order to develop e-learning in the university we need to understand the texts and practices that are involved in learning and teaching using online and web-based technologies.